Community-based water tenure in equitable and transformative drought resilience - van Koppen, Barbara; Mweemba, C. E.; Amarnath, Giriraj; Schreiner, B. (Elsevier, 2024)
In the search for promising pathways for equitable and transformative climate adaptation in low-income rural areas, the present study focuses on resilience to more variable and less predictable availability of precipitation and water resources. Equitable water governance is conceptualized as formal and informal polycentric decision-making that narrows infrastructure inequities and ensures equitable water resources allocation. Focusing on recognitional and procedural equity, vulnerable women’s and men’s community-based water tenure is starting point. Partnering with government in Zambia and with the Water Integrity Network in Kenya, field research in three communities in rural Zambia and in rural communities and a small town sharing several schemes in Kenya is conducted. These studies recognized horizontal polycentricity of community-based water tenure by identifying common features: communities’ age-old drought resilience coping strategies to meet daily domestic water needs and daily or seasonal small-scale productive water needs, by tapping water from surface- and groundwater sources through multi-purpose infrastructure, both self-financed and publicly supported, and by ‘sharing’ water ‘in’ within the community and ‘sharing out’ with neighbouring communities and powerful third parties. Procedural equity implies inclusive, locally-led planning, design and implementation in polycentric vertical governance with governments and other support agencies from local to national level and vice versa. The four interventions studied were the installation of a a solar-powered borehole for multiple uses and local government’s institutional framework for potential replication in Zambia, and post-construction support of small water systems and a planned megadam in Kenya. Further research on similar transformative approaches elsewhere is recommended.